2007
DOI: 10.1155/2007/620396
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Anthralin From the Roots of Rhubarb Plant (Rheum palmatum)

Abstract: Anthralin is medically and chemically an important compound which can be found in rhubarb roots. Anthralin and anthralin derivatives have been used as antipsoriatic drugs. In this research, pure anthralin was isolated from the rhubarb roots by maceration and Soxhlet extraction methods in various polar and non-polar solvents.Successive TLC and column chromatography on silica gel with chloroform as the mobile phase afforded two distinct fractions with R f = 0.54 and 0.61. The 1 HNMR, 13 CNMR, IR, UV and MS spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Chemical screening or metabolite profiling protocols of herbal extracts using hyphenated techniques, particularly, the LC/UV, LC/MS and LC/NMR serve to distinguish between novel and already known bioactive principles in the course of search for new lead compounds from medicinal plants. Furthermore, spectroscopic techniques such as UV/VIS and IR spectrophotometry, carbon and proton NMR, MS and x-ray diffraction are applied for elucidation of structural conformations of bioactive principles (Ashnagar et al, 2007;Ejele et al, 2012;Ejele et al, 2014;Karayil et al, 2014; http://www.eolss.net/Sample-Chapters/C03/E6-79-04.pdf). Also, chemical techniques involving hydrolysis, formation of derivatives and hydration reaction coupled with structural modifications of bioactive principles are applied to establish structure/function relationship (http://www.eolss.net/Sample-Chapters/C03/E6-79-04.pdf).…”
Section: Drying and Grinding Of Plant Materialmentioning
confidence: 99%
“…Chemical screening or metabolite profiling protocols of herbal extracts using hyphenated techniques, particularly, the LC/UV, LC/MS and LC/NMR serve to distinguish between novel and already known bioactive principles in the course of search for new lead compounds from medicinal plants. Furthermore, spectroscopic techniques such as UV/VIS and IR spectrophotometry, carbon and proton NMR, MS and x-ray diffraction are applied for elucidation of structural conformations of bioactive principles (Ashnagar et al, 2007;Ejele et al, 2012;Ejele et al, 2014;Karayil et al, 2014; http://www.eolss.net/Sample-Chapters/C03/E6-79-04.pdf). Also, chemical techniques involving hydrolysis, formation of derivatives and hydration reaction coupled with structural modifications of bioactive principles are applied to establish structure/function relationship (http://www.eolss.net/Sample-Chapters/C03/E6-79-04.pdf).…”
Section: Drying and Grinding Of Plant Materialmentioning
confidence: 99%
“…In particular, the dried root powder of the madder ( Rubia tinctorum L.) was separately mixed in methanol, ethanol, water, benzene, methylene chloride and toluene solvents, and the extraction process was performed for 8 hours, after which the solvents were removed by evaporation and pure alizarin was obtained through an isolation step. The experimental result indicated that the Soxhlet extraction method had the most adequate yield percentage of anthraquinone (14.2%) in methanol, whereas the maceration method released a low anthraquinone yield rate (5.2%) in methanol after 48 hours 66 …”
Section: Extraction Methods Of Alizarin From Rubiaceae Family Plantsmentioning
confidence: 99%
“…For instance, Ashnagar et al obtained alizarin dye from madder ( Rubia tinctorum L.) by separately immersing 100 g of ground roots in 350 mL of water, ethanol, methanol, benzene, methylene chloride and toluene for 48 hours at room temperature, followed by filtration, to obtain the clear dye solutions. As a result, the extraction yields were 2.8%, 4.3%, 5.2%, 3.5%, 4.2% and 3.4%, respectively 66 . Similarly, Santis and Moresi carried out alizarin extraction from Rubia tinctorum L. by individually mixing its root powder in 20 cm 3 of acetone, ethanol, methanol, water and ether solvents for 12 hours at 25°C.…”
Section: Extraction Methods Of Alizarin From Rubiaceae Family Plantsmentioning
confidence: 99%